A Literature Review: Nutritional Potential, Antinutritional Factors, and Flavonoids of Chaya (Cnidoscolus Aconitifolius) Leaves as Ruminant Feed - Putri, Aprillia Ika; Marjuki; Hartutik (Jurnal Nutrisi Ternak Tropis, 2025)
Chaya (Cnidoscolus aconitifolius) leaves have gained attention as an alternative feed for ruminants due to their high nutritional value and beneficial bioactive compounds. This review examines their nutritional content, antinutritional factors, and flavonoid compounds. Chaya leaves are rich in protein (14–29%), fiber, vitamins, and minerals that are essential for livestock productivity. However, certain antinutritional compounds, such as cyanogenic glycosides, tannins, and saponins, may limit their utilization unless they are properly processed. Processing methods like drying and fermentation can help reduce these compounds. Additionally, the flavonoids found in Chaya leaves demonstrate antioxidant and anti-inflammatory properties, which could potentially enhance animal health. Therefore, Chaya leaves show promise as a sustainable feed resource, although further research is needed to optimize their use while minimizing the effects of antinutritional factors.